Memahami Tantangan dan Strategi Pengembangan Profesionalisme Guru dalam Mengajar Pendidikan Jasmani Adaptif - Nika Fellisiana Putri; Pungki Indarto (Jurnal Syntax Admiration, 2024)
Physical, social and personal health, especially for children with special needs. This is important so that children can develop optimally according to their abilities. However, the teaching of adaptive physical education also brings many challenges for teachers. Limited space and equipment make it difficult to achieve an inclusive environment for all students. To meet these challenges, teachers must improve their professional skills through specialized training, teamwork, comprehensive curriculum development, improved accessibility of facilities and individualized teaching methods. The purpose of this teacher professional development strategy is to improve teachers' skills in the field of adaptive sports education and ensure that all students, including students with special needs, have a good opportunity to enter physical education. In this way, teachers can provide educational services according to the needs and abilities of each student. In addition, this study uses qualitative research methods to describe and analyze phenomena, events, social activities, attitudes, beliefs, perceptions and thoughts of individuals or groups. Through extensive data collection and in-depth analysis, this study provides a better understanding of the challenges and strategies related to teacher professional development in the field of adaptive physical education. Therefore, adaptive physical education plays an important role in improving the physical, social and emotional well-being of students with special needs. However, to achieve this, further efforts are needed to develop teachers' professional skills and make physical education accessible to all students.